Fluid Flow Problems - Ali, Farhad (IntechOpen, 2019)
In physics and engineering, fluid dynamics is a subdiscipline of fluid mechanics that describes the flow of fluids, liquids, and gases. It has several subdisciplines, including aerodynamics (the study of air and other gases in motion) and hydrodynamics (the study of liquids in motion). Fluid dynamics has a wide range of applications, including calculating forces and moments on aircraft, determining the mass flow rate of petroleum through pipelines, predicting weather patterns, understanding nebulae in interstellar space and modeling fission weapon detonation. In this book, we provide readers with the fundamentals of fluid flow problems. Specifically, Newtonian, non-Newtonian and nanofluids are discussed. Several methods exist to investigate such flow problems. This book introduces the applications of new, exact, numerical and semianalytical methods for such problems. The book also discusses different models for the simulation of fluid flow.